The spontaneous ideation for the nascent entrepreneurs: The reasonings, learning loops and outcomes matrices, models and visual tools for collaborating with AI in support of innovative sustainable business solutions - Russ, Meir (Journal of Management and Business Education, 2025)
The paper summarizes in a step-by-step guiding format a model for developing new ideas (Ideation) that can be used to form a new spontaneous venture or accelerate the development of a new service or product, augmenting sustainable solutions. The proposed guidelines are widely used and can be applied in tandem with other prevalently available models or tools. The paper intends to serve as a resource for entrepreneurs and innovators, as well as for teaching and training nascent entrepreneurs. The author has used the framework and the tools described here in numerous Ideation and Entrepreneurship classes taught for over a decade in several countries around the world. The purpose is to provide an effective and efficient set of tools, models, and techniques that can assist the entrepreneur in her accelerated journey to create and achieve her dreams. Such tools are the matrix of Reasonings-Outcomes, the matrix of Reasonings-Learning Loops, and the matrix of Outcomes-Learning Loops introduced here for the first time. The paper adds an academic review when and where appropriate, as well as a discussion of how the incorporation of Artificial Intelligence (AI) can broaden the scope, accelerate the process in an effective and efficient way by providing practical, innovative, and sustainable illustrations and examples. This is exemplified by developing business models in a circular economy of a socially responsible business idea.